The Influence of Product Quality, Price & Service Quality on Consumer Satisfaction at Palekko Sidenreng Eating Houses in Sidrap District - Fitria, Safira; Kurniawan, Agung Widhi; Wardhana Haeruddin, Muhammad Ilham` (Economics and Business Journal (ECBIS), 2023)
This research aims to determine the partial influence of product quality, price and service quality on consumer satisfaction at the Palekko Restaurant in Sidenreng Rappang Regency. The number of samples taken was 100 respondents. The results of the research show that service quality, price and product quality have a significant effect on consumer satisfaction at the Palekko Sidenreng Restaurant in Sidenreng Rappang Regency, based partially on the calculation results that the t-calculated value of the product quality variable is ( 6.435), the t-calculated value of the price variable is (3.223) and the t-calculated value of the service quality variable (3.752) is greater than the t-table value (1.660) and the sig value of all variables is smaller than 0.05. Simultaneously, service quality, price and product quality have a significant effect on consumer satisfaction at the Palekko Sidenreng Restaurant in Sidenreng Rappang Regency. The calculation results show that the F-count value = 30,946 is greater than the F-table value = 2.70 (30,946 > 2.70) and significance value = 0.000 (smaller than α = 0.05). (0.000 < 0.05).